25-Hydroxycholecalciferol response to single oral cholecalciferol loading in the normal weight, overweight, and obese. Issue 8 (August 2016) - Camozzi, V.; Frigo, A.; Zaninotto, M.; Sanguin, F.; Plebani, M.; Boscaro, M.; Schiavon, L.; Luisetto, G.
Abstract Summary After a single cholecalciferol load, peak serum 25-hydroxycholecalciferol (25OHD) is lower in individuals with a higher body mass index (BMI), probably due to it being distributed in a greater volume. Its subsequent disappearance from the serum is slower the higher the individual's BMI, probably due to the combination of a larger body volume and a slower release into the circulation of vitamin D stored in adipose tissue. Introduction The aim of the study is to examine 25-hydroxycholecalciferol (25OHD) response to a single oral load of cholecalciferol in the normal weight, overweight, and obese. Methods We considered 55 healthy women aged from 25 to 67 years (mean ± SD, 50.8 ± 9.5) with a BMI ranging from 18.7 to 42 kg/m2 (mean ± SD, 27.1 ± 6.0). The sample was divided into three groups by BMI: 20 were normal weight (BMI ≤ 25 kg/m2 ), 21 overweight (25.1 ≤ BMI ≤ 29.9 kg/ m2 ), and 14 obese (BMI ≥ 30 kg/m2 ). Each subject was given 300, 000 IU of cholecalciferol orally during lunch. A fasting blood test was obtained before cholecalciferol loading and then 7, 30, and 90 days afterwards to measure serum 25OHD, 1, 25 dihydroxyvitamin D [1, 25 (OH)2 D], parathyroid hormone (PTH), calcium (Ca), and phosphorus (P). Participants' absolute fat mass was measured using dual energy X-ray absorptiometry (DEXA). Results The fat mass of the normal weight subjects was significantly lower than that of the overweight, which in turn was lower than that of the obese participants. Serum 25OHD levels increased significantly in all groups, peaking 1 week after the cholecalciferol load. Peak serum 25OHD levels were lower the higher the individuals' BMI. After peaking, the 25OHD levels gradually decreased, following a significantly different trend in the three groups. The slope was similar for the overweight and obese, declining significantly more slowly than in the normal weight group. In the sample as a whole, there was a weakly significant negative correlation between fat mass and baseline 25OHD level, while this correlation became strongly significant at all time points after cholecalciferol loading. Conclusions The lower peak 25OHD levels seen in the obese and overweight is probably due to the cholecalciferol load being distributed in a larger body volume. The longer persistence of 25OHD in their serum could be due to both their larger body volume and a slower release into the circulation of the vitamin D stored in their adipose tissue.